The link between vocational training and higher education in Switzerland, Austria, and Germany - Nikolai, Rita [Verfasser]; Ebner, Christian [Verfasser] (My University, 2012)
"In recent years, Germany, Austria, and Switzerland have adopted different strategies to increase permeability between dual vocational training and higher education. Germany relies on the consideration of occupational competencies for higher education admission, while Switzerland and Austria have introduced double-qualification certificates that enable the simultaneous acquisition of a dual vocational degree and a higher education entrance qualification." This contribution analyzes these differences in the organization of the links between VET and higher education in the three countries. Using the varieties of capitalism (VoC) approach, the special significance of firms as the drivers and initiators of institutional change in the VET system is highlighted. The varying interests of small and large firms play a crucial role in this context. (BIBB-Doku, Autorenreferat)
Keywords: G 2.5.3 Anschlussfähigkeit von Bildungsgängen; S 1.3.4 Doppelqualifizierende Bildungsgänge; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.2.1 Westeuropa; Durchlässigkeit im Bildungssystem; Doppelqualifikation; Internationaler Vergleich; Bundesrepublik Deutschland; Österreich; Schweiz